Un Sistema Integrato per la Gestione e la Rielaborazione in Ambiente Tridimensionale della Documentazione Prodotta dalle Indagini Archeologiche presso le Pendici Nord-orientali del Palatino - Brienza, Emanuele; Fornaciari, Lorenzo (Archeomatica, 2020)
The urban landscape enclosed between the valley of the Colosseum, Palatine Hill and Velia, despite being the result of multiple urban interventions that have taken place over time, still retains a plan of use and an architectural context that dates back to the 4th century. a.D. Obviously what we see is the result of demolitions and excavation operations that have affected the area from the post-ancient age until today. Furthermore, if it is true that the Flavian Amphitheater, the Arch of Constantine and the Temple of Venus and Rome have partially (good or bad) survived the spoliation and vicissitudes of the area, these live as individual monuments, without the urban connective tissue in which they fell in ancient times. In this context, the archaeological research conducted since 1986 at Meta Sudans by the Sapienza University of Rome, under the direction of Prof. Clementina Panella, has affected a large area, between the Arch of Constantine and the Hadrianic base of the Colossus, in order to investigate the ancient vicissitudes of the area: the intent was to find traces of its history, from the earliest human acquaintances to today, and to reconstruct the various forms assumed here by ancient topography. Subsequently, from 2001 to 2017, the investigations moved along the north-eastern slopes of the Palatine with the aim of reconnecting the valley with the Palatine hill and the Forum, reconstructing the connections that the post-ancient demolitions and especially those of the fascist age they had partially stopped. All this research has made the attempt of a general reconstruction of the historical events of the urban landscape practicable, from its first anthropization to the present day, aimed at its correct knowledge, conservation, enhancement and dissemination. Due to space problems, it is not possible to summarize the various chronological phases and the main historical events of the area here. We can only underline how the first traces of settlement, referable to a village of huts from the Iron Age, followed, uninterrupted and numerous over the centuries, a seriesof construction and destruction of urban blocks that overlap and obliterate each other.